An Evaluation On Dual Energy X-ray Transmission Sorting And Its Measurement Precision For Coal - Ariane Kuerten; Paulo Conceição; Carlos Sampaio; Carlos Petter (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
The Sensor Based-Sorting technology is an emerging technology applied in mineral separation and concentration. The technique consists in using a method known as Dual Energy X-ray Transmission sorting (DE-XRT). The particle's position over the conveyor belt was evaluated and, despite de variability of results, shows that there is no a position with greater accuracy on the sensor's reading. Results obtained indicated that DE-XRT sorting technology was able to significantly reduce the mass and the ash content of the ore feed, being an interesting option for reduction of costs and improvement of coal quality in beneficiation plants.